2019
DOI: 10.3390/v11020194
|View full text |Cite
|
Sign up to set email alerts
|

Priorities, Barriers, and Facilitators towards International Guidelines for the Delivery of Supportive Clinical Care during an Ebola Outbreak: A Cross-Sectional Survey

Abstract: During the Ebola outbreak, mortality reduction was attributed to multiple improvements in supportive care delivered in Ebola treatment units (ETUs). We aimed to identify high-priority supportive care measures, as well as perceived barriers and facilitators to their implementation, for patients with Ebola Virus Disease (EVD). We conducted a cross-sectional survey of key stakeholders involved in the response to the 2014–2016 West African EVD outbreak. Out of 57 email invitations, 44 responses were received, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…In previous emergency situations, traditional care has been restricted by infection prevention measures, increased workload, and limited resources. [2][3][4][5][6] We have shown that during the COVID-19 outbreak in the UK, healthcare workers faced similar difficulties which led to drastic changes in care provision. While these changes were difficult for patients and families, the impact on healthcare workers had not been previously explored.…”
Section: What This Study Addsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous emergency situations, traditional care has been restricted by infection prevention measures, increased workload, and limited resources. [2][3][4][5][6] We have shown that during the COVID-19 outbreak in the UK, healthcare workers faced similar difficulties which led to drastic changes in care provision. While these changes were difficult for patients and families, the impact on healthcare workers had not been previously explored.…”
Section: What This Study Addsmentioning
confidence: 99%
“… 3 Reduced staff and resources led to similar consequences during the Ebola outbreak in West Africa. 4 , 5 Traditional care delivery can also be impacted when a focus on saving the greatest number overshadows the management of those at the end-of-life. 6 …”
Section: Introductionmentioning
confidence: 99%
“…Policies Require flexibility and rapid changes to systems and policies 5,10 Limiting visitor hours/numbers 5,10 Change in admission criteria 5 Systems of daily telephone support for families 5 Stopping volunteer services 10 Palliative care and hospice care should be part of the national and Local epidemic/pandemic planning 3,4 Training and protocols Palliative care protocols for nonspecialist staff on management of symptoms and psychological support are essential 3,4,6,7 Training for site leads in the use of the protocols 4 Education and training for nonspecialist staff in basics of palliative care, 8 including in communication and bereavement counseling 11 Consider separate guidelines for specific populations such as people in care homes and those with intellectual disabilities 3 Communication and coordination Sharing of protocols, advice, and standards of care within organizations 6 Identification of a decision maker to improve communication, particularly where multiple health professionals may be involved outside their usual practice 8 Rapid triage to assess likelihood of response to treatment 3…”
Section: Systemsmentioning
confidence: 99%
“…Standardized information collection 9 Continuous monitoring and evaluation to inform operational changes or quality of services 9 Staff Deployment of staff Flexibility of deployment, such as moving staff from acute setting to the community 5,12 Sufficient staff numbers 8 Restricting contact with volunteers for infection control, 5,10 whereas acknowledging volunteers are integral to the interdisciplinary model in palliative care and can make important contributions to psychosocial and bereavement care 10 Skill mix of staff Involving spiritual care and chaplains in the pandemic response 3,4 Involving psychologists with expertise in palliative care 3 Ensuring resilience of staff Facilitating camaraderie among staff important to minimize negative psychosocial effects on staff, which include distress about risks of contracting the disease, grieving relatives, or friends while working 6 Measures to improve connectedness among staff 11 Training in communication and bereavement counseling 11 Measures to help health care workers deal with stress 11 Space Moving to community provision Consider shifting resources from inpatient to community settings where demand may be higher 5,12 Consider the setup of community care centers to expand outside hospital with standardized designs, include monitoring and evaluation instruments, and make use of training and supervision manuals. Community engagement to foster trust is important 9…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation